Pengaruh Permainan Ular Tangga dalam Meningkatkan Pengetahuan Menjaga Kesehatan Gigi dan Mulut Di SD Islam Al-Jannah Kabupaten Indramayu - Dea Sutami; Musri Amurwaningsih; Prima Agusmawanti (YARSI Dental Journal, 2025)
Abstract Introduction: School-age children have a high risk of tooth decay because they often consume foods and drinks that can damage teeth. This is caused by a lack of understanding of how to maintain oral health, so health promotion is needed with interesting methods, one of which is through snakes and ladders games. Objective: This study aims to analyze the effect of snakes and ladders game on increasing knowledge about oral health in students of Al-Jannah Islamic Elementary School, Indramayu Regency. Material and Method: This study used a pre-experimental design with the One Group Pre-Test and Post-Test method. The research sample was selected using simple random sampling technique based on inclusion and exclusion criteria, with a total of 59 children. Activities were carried out in one meeting and data were collected through pre-test and post-test. Results: The results showed a significant difference (p<0.05) between the data before and after counseling using snakes and ladders game, which means that snakes and ladders game has an influence on increasing students' knowledge about oral health. Conclusion: Health counseling through snakes and ladders game proved to be effective in increasing understanding of oral health in students of Al-Jannah Islamic Elementary School, Indramayu Regency.